Les conséquences de la crise sanitaire sur les relations de travail - Louis Alexandre Erb; François Pierre Reynaud (Revue de la Régulation)
This contribution discusses implications of the lockdown on working conditions working relationship for employees. It uses data from first surveys on the French lockdown. This unique period has generated a large economic shock that led to significant changes on the employees’ activity and the working conditions and institutions (the labour-wage nexus). In some cases, employers desire to maintain the activity in spite of the sanitary context and the necessity to preserve the health of workers. Usually, social differences by gender are overlooked, for instance, caring for children, also being confined at home, is not foreseen. In other cases, new ways of working appear such as the development of remote working and short-time working to tackle mobility restrictions. Even if the continuities and the changes we observe had not been planned, they may announce a new labour-wage nexus in the long run.